Optimal systemic combined design and control of an automated wind energy conversion system. Issue 2 (April 2023) - Tounsi, Souhir
In this paper, is presented a design and control toll of electromechanical braking system dedicated to wind energy conversion chain. The braking system makes it possible to apply pressure strength at the level of the rotating shaft near to the propeller of the wind turbine. This pressure force is transformed into a dry friction force via the mechanical part of the braking system consisting of a piece of brake lining and steel of the rotating shaft of the propeller. A program of dimensioning by the analytical method of a permanent magnet linear motor structure is developed. The interactions between this program and the braking system control algorithm are taken into account. The integration of the global model under the Matlab-Simulink simulation environment allows full validation of the presented study.